Strain-dependent effects of clinical echovirus 30 outbreak isolates at the blood-CSF barrier - Dahm, Tobias; Morozov, Vasily; Hansman, Grant S.; Weiß, Christel; Stump-Guthier, Carolin; Schroten, Horst; Schwerk, Christian; Tenenbaum, Tobias; Rudolph, Henriette (Journal of neuroinflammation, 2018)
Echovirus (E) 30 (E-30) meningitis is characterized by neuroinflammation involving immune cell pleocytosis at the protective barriers of the central nervous system (CNS). In this context, infection of the blood-cerebrospinal fluid barrier (BCSFB), which has been demonstrated to be involved in enteroviral CNS pathogenesis, may affect the tight junction (TJ) and adherens junction (AJ) function and morphology.
Gesehen am 04.04.2018